Morphological and isozyme characterisation of Arachis pintoi Krap. et Greg. nom. nud. germplasm - Maass, Brigitte L.; Torres González, Alba Marina; Ocampo Nahar, César H. (Springer, 1993)
Arachis pintoi, a wild perennial relative of the peanut, originated in Brazil, is of increasing importance to pasture improvement in the tropics. Its available genetic base, however, is very narrow, and intensive collection is being carried out. This study aimed to characterise the existing eight accessions in the CIAT germplasm collection in order to describe the existing variation, identify plant types, and discover possible duplicates. Morphological characterization, based on 60 morphological descriptors, demonstrated that variation exists. Numerical taxonomic techniques were used to rank the importance of these descriptors. Cluster analysis, conducted on those pre-selected morphological characters, grouped the accessions into two major plant types: one homogenous, and the other falling into four distinct subgroups. Polyacrylamide gel electrophoresis (PAGE) was applied to root-tip tissue. Isozyme characterization by PAGE showed polymorphisms in the isozymes alpha-EST, ACP, GOT, and DIA. When analysed together, the four isozymes could uniquely distinguish every accession of A. pintoi held in the CIAT germplasm collection. Correspondence and cluster analyses of these isozyme patterns showed the morphologically homogenous plant type to be heterogeneous, and the heterogenous morphotype to have similar banding patterns. The lack of continuous patterns of variation in heath morphology and isozymes manifests the need for further germplasm collection of A. pintoi.